A comparative study on the impact of Gd2O3 burnable neutron absorber in UO2 and (U, Th)O2 fuels - Uguru, E.H.; Sani, S.F. A.; Khandaker, Mayeen Uddin *; Rabir, M. H.; Julia, A. K. (Elsevier, 2020)
The performance of gadolinium burnable absorber (GdBA) for reactivity control in UO2 and (U, Th)O2 fuels and its impact on spent fuel characteristics was performed. Five fuel assemblies: one without GdBA fuel rod and four each containing 16, 24, 34 and 44 GdBA fuel rods in both fuels were investigated. Reactivity swing in all the FAs with GdBA rods in UO2 fuel was higher than their counterparts with similar GdBA fuel rods in (U, Th)O2 fuel. The excess reactivity in all FAs with (U, Th)O2 fuel was higher than UO2 fuel. At the end of single discharge burn-up (~ 49.64 GWd/tHM), the excess reactivity of (U, Th)O2 fuel remained positive (16,000 pcm) while UO2 fuel shows a negative value (−6,000 pcm), which suggest a longer discharge burn-up in (U, Th)O2 fuel. The concentration of plutonium isotopes and minor actinides were significantly higher in UO2 fuel than in (U, Th)O2 fuel except for 236Np. However, the concentration of non-actinides (gadolinium and iodine isotopes) except for 135Xe were respectively smaller in (U, Th)O2 fuel than in UO2 fuel but may be two times higher in (U, Th)O2 fuel due to its potential longer discharge burn-up